ATLAS Run 1 searches for direct pair production of third-generation squarks at the Large Hadron Collider - Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Aben, R; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; Acharya, B; et al. (Springer Berlin Heidelberg, 2015)
This paper reviews and extends searches for the direct pair production of the scalar supersymmetric partners of the top and bottom quarks in proton–proton collisions collected by the ATLAS collaboration during the LHC Run 1. Most of the analyses use 20 fb-1 of collisions at a centre-of-mass energy of √s = 8 TeV, although in some case an additional 4.7 fb-1 of collision data at √s = 7 TeV are used. New analyses are introduced to improve the sensitivity to specific regions of the model parameter space. Since no evidence of third-generation squarks is found, exclusion limits are derived by combining several analyses and are presented in both a simplified model framework, assuming simple decay chains, as well as within the context of more elaborate phenomenological supersymmetric models.